PENGARUH PROGRAM DIALOG INTERAKTIF “HALO KALTIM” RADIO REPUBLIK INDONESIA TERHADAP TINGKAT KEPUASAN PENDENGAR - Heriyanto, Eddy Soegiarto K, dan Selviana Meikayanti (Prodi Ilmu Administrasi Negara, 2020)
The growth of the mass media industry in recent years has shown increasingly tight competencies. At first there were only electronic media and print media such as radio, television and newspapers. But now there are online media via the Internet such as websites or web. The development of online media users in Indonesia makes print media, such as radio, should present the best breakthrough for the target audience, to survive in the future.This research is intended to examine the effect of the program quality